(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article analyses certain implications for global security architecture of using international law as an instrument of power by states in the digital age. The author’s point of view is that in conditions of rising geopolitical competition, using international legal warfare to achieve strategic objectives increases the risks and threats for stability of international order. The scientific paper is divided into four sections. In the introduction, the main problem related to international lawfare is defined, including its significance for our international community. The first section defines a legal research methodology that is applied. The second conceptualizes international legal warfare. The third examines different cases of lawfare that have negative implications for global security architecture. The fourth deals with emerging and disruptive technologies that define geopolitical competition and how they relate to lawfare. In the conclusion, an assessment is provided regarding developments of international law, including its normative role for the global security architecture. The paper makes few recommendations for preservation of current international order, which is being challenged by the growing number of legal warfare practices between various geopolitical actors.